Modified Sijunzi granule decreases post-weaning diarrhea in Rex rabbits via promoting intestinal development - Li, Dongbo; Wang, Yueli; Liu, Ning; Chen, Shiqi; Liu, Hanzhong; Wang, Ping; Yu, Zhiju; Shu, Gang; Lin, Juchun; Zhang, Wei; Peng, Guangneng; Zhao, Ling; et al. (Frontiers in Veterinary Science, 2022)
Traditional Chinese medicine (TCM) formulas can be adjusted on the basis of TCM basic theory to achieve the best curative effect, especially for diseases with complex pathogenesis, such as Post-weaning Diarrhea (PWD). Shugan Jianwei Sijunzi decoction (SJ-SJZD) can be recognized as modified Sijunzi Decoction (SJZD) supplemented with Astragalus mongholicus Bunge, Bupleurum chinense DC, Citrus × aurantium L. and Crataegus pinnatifida Bunge(fruit) in a fixed dosage ratio. The inactive ingredients were subsequently added to make granule, which was Shugan Jianwei Sijunzi granule (SJ-SJZG). Previous studies have confirmed the antagonism of SJ-SJZG to PWD. However, the mechanism of SJ-SJZG protective effects on small intestine in weaned Rex Rabbits remained unclear. Animals were randomly divided into negative control (NC), low dose (LD), medium dose (MD), high dose (HD), positive control (PC). SJ-SJZG significantly increased the intestinal length and the jejunum villi length. The SIgA level was statistically increased in duodenum and jejunum with the ELISA. Immunohistochemical detection showed that SIgA protein expression was also increased significantly in jejunum. Meanwhile, the relative expression of Zo1 in duodenum and jejunum of SJ-SJZG group increased significantly. SJ-SJZG significantly increased the relative expression of Occludin in duodenum and jejunum as well. Moreover, real-time PCR results showed a significant increase of GLUT2 and SGLT1 relative expression in ileum. SJ-SJZG could also obviously enhanced the expression of GLUT2 in jejunum and the expression of SGLT1 in duodenum. In conclusion, SJ-SJZG had been proved to be effective in promoting the development of small intestine and improving the immunity of small intestine. Moreover, SJ-SJZG could ensure the integrity of mucosal barrier and increase the ability of intestine to absorb glucose in small intestine.